2013
DOI: 10.1080/0144929x.2012.745606
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of mHealth service quality on satisfaction, continuance and quality of life

Abstract: U. (2013). Modelling the impact of mHealth service quality on satisfaction, continuance and quality of life. Behaviour and Information Technology, OnlineFirst 1-17.Modelling the impact of mHealth service quality on satisfaction, continuance and quality of life AbstractUnderstanding the impact of service quality on economic and social outcomes is critical to extend the focus of IT service research. This study evaluates the impact of quality on both these dimensions in mHealth using a cross disciplinary approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 75 publications
4
36
0
Order By: Relevance
“…We also observed that theories have been employed to study IT continuance use intention, such as TAM [27,28]. To understand the underlying factors that impact technology continuance use, IT continuance use behavior has been examined in research with theories, such as the extended expectation-confirmation model [52], theory of planned behavior [53], unified theory of acceptance and use of technology [54] and the cognition-affection-conation chain [55].…”
Section: Continuance Use Intentionmentioning
confidence: 99%
“…We also observed that theories have been employed to study IT continuance use intention, such as TAM [27,28]. To understand the underlying factors that impact technology continuance use, IT continuance use behavior has been examined in research with theories, such as the extended expectation-confirmation model [52], theory of planned behavior [53], unified theory of acceptance and use of technology [54] and the cognition-affection-conation chain [55].…”
Section: Continuance Use Intentionmentioning
confidence: 99%
“…Even if there are no studies that apply the value perspective to the mobile health context, there were previous works on service quality and users' perceptions of mobile health (e.g. Akter et al, 2013b). Because these works identified functional attributes as salient for mobile health service quality, this current study quantitatively investigates sub-dimensions of functional value in mobile health.…”
Section: Introductionmentioning
confidence: 99%
“…In an aging and economically developing society, the level of demand for greater quality and wider availability of healthcare services has increased. However, problems such as high costs, uneven quality levels and inequalities in terms of access to healthcare plague the current healthcare industry (Akter et al, 2013b). In this context the rapid growth of information communications technology (ICT) is receiving attention as a potential solution to resolve the issue of limited access to healthcare and to satisfy the need to reduce healthcare costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the IS success model [9, 16] and other evidence [13, 17, 25], HIS attributes including system quality, information quality, and service quality may prove to be important antecedents of user satisfaction.…”
Section: Introductionmentioning
confidence: 99%